Influence of environmental temperature on the elasticity of rigid catenary and pantograph-catenary current collection quality of subway lines - YANG Gang; LYU Kun; KONG Guowei; SHEN Xin; LI Fu (机车电传动)
In recent years, there have been large-scale incidents of abnormal wear on subway pantographs and catenaries across China, especially in winter. In 2022, more than 30 subway lines nationwide encountered this issue, resulting in economic losses amounting to hundreds of millions of yuan. In order to study the influence of environmental temperature on the pantograph-catenary relationship, a finite element model of the rigid catenary of a subway line was established. The stiffness curve of the catenary was calculated at ambient temperatures of -20~20 °C. The pattern of influence of environmental temperature on the stiffness of the catenary was analyzed. Then, a dynamic model of subway pantograph-catenary coupling with variable stiffness was established, and its accuracy was verified according to EN 50119 and other standards. The pantograph-catenary contact force was calculated under the conditions of ambient temperatures of -20~20 °C, train running speed of 40~90 km/h, pantograph static lifting force of 70~160 N, and stuck positioning clamps. Furthermore, the influence of environmental temperature on the pantograph-catenary contact force and the pantograph-catenary current collection quality was analyzed. The results show that there is a strong positive correlation between environmental temperature and the pantograph-catenary contact force and current collection quality. When the environmental temperature is below 0 °C, the pantograph-catenary current collection index will seriously deteriorate; stuck wire clamps will have a negative impact on the pantograph-catenary contact force and current collection quality, and the higher the train running speed, the greater the impact will be.